Tormanov N.T., Tuleuhanov S.T., Ursheeva B.I. The role of environmental medicine in the study of the inﬂuence of environmental factors on human health: Al-Farabi Kazakh National University, Almaty, Kazakhstan (Eurasian Journal of Ecology, 2018)
This article discusses the factors that affect the environment on humanhealth and disease processes. Environmental factors can be divided intothree groups. These include atmospheric factors (based meteorological)kosicheskie factors (radiation), gellurgicheskie factors (land relief). This iswhat we will say in our article. We all know that anthropogenic factorsaffect the environmental crisis. Climatic disasters on the earth at a globallevel not only affects human health, they affect the population of all livingbeings and cause their destruction. Thus giving environmental educationin schools and universities especially in the field of medicine, specialtyecology, biology, biotechnology, medical and preventive-business, it isvery important and there is a need to make «Environmental Medicine» inthe school curriculum.Key words: pathology, pollution, environment, environmental medicine, the environment, space.